Neurodevelopmental Outcome in A Child With West Syndrome On Multidisciplinary Intervention – A Case Report (Bangladesh Journal of Child Health, 2022)
West syndrome is a triad of infantile spasms with hypsarrhythmia and developmental regression. It results in a poor neurodevelopmental outcome due to delayed diagnosis and treatment which is further compounded by a delay in referral to multidisciplinary interventions. Our case was a male child with west syndrome who came to us at 3 years of age with neurodevelopmental concerns of global developmental delay with features of autism spectrum disorder. Based on thorough developmental evaluation he was started on an individualised, short term, goal oriented multidisciplinary therapy with physiotherapy, occupational therapy and parental counselling for his neurodevelopmental concerns. As a result improvement was noted in his motor as well as socioemotional skills. Early intervention with multidisciplinary therapy with adherence by motivated parents is essential for a better neurodevelopmental outcome in a case of west syndrome.BANGLADESH J CHILD HEALTH 2021; VOL 45 (3) : 186-190